The nothing place - Spence, Eleanor; Spence, Geraldine (New York Harper & Row, 1973)
Learning to accept his partial deafness is bad enough, but having to adjust to a new neighborhood and a bunch of do-good friends is almost too much for Glen.
Keywords: Physically handicapped -- Fiction; Deaf -- Fiction; Australia -- Fiction